The role of prenatal stress and maternal trauma responses in predicting children’s mental health during war - Karen Yirmiya; Amit Klein; Shir Atzil; Noa Yakirevich-Amir; Rena Bina; Inbal Reuveni (European Journal of Psychotraumatology)
Background: The negative effects of prenatal stress on children’s development and the buffering effects of maternal behaviour are well documented. However, specific maternal responses to trauma, particularly among families experiencing cumulative stressors during pregnancy and early childhood, remain less understood.Objective: This study investigated the interplay between prenatal stress in the context of the coronavirus disease 2019 (COVID-19) pandemic and consequent maternal trauma responses and children’s difficulties in the context of war-related trauma.Methods: We recruited 318 pregnant women in Israel during the first wave of the COVID-19 pandemic (Time 1). Prenatal depression, anxiety, and COVID-related stress symptoms were assessed. When children were approximately 3.5 years old (SD = 0.02), the mothers were asked to report on parental responses related to the ongoing war and their child’s emotional and behavioural difficulties (Time 2). Structural equation modelling was used to examine how maternal trauma responses mediate the association between prenatal stress-related mental health symptoms and children’s difficulties during war.Results: Maternal prenatal depressive, anxious, and COVID-19-related stress symptoms predicted maladaptive maternal trauma responses during the war, which in turn were associated with increased emotional and behavioural problems in their children. Among the specific maternal trauma-related responses examined, cognitive avoidance and overprotectiveness were the only behavioural responses during the war significantly associated with children’s difficulties.Conclusions: Our study highlights the impact of pandemic-related prenatal stress on maternal responses and children's difficulties during war, emphasizing the importance of identifying at-risk families as well as developing targeted interventions that mitigate negative parenting responses, particularly avoidance and overprotection.